Influences of Discriminatory Incidents on Immigrants’ Attitudes Toward German Society - Döring, Jan (International Journal of Conflict and Violence (IJCV), 2007)
This article presents findings from a quantitative survey (N = 301) to evaluate the impact discriminatory incidents have on the attitudes of immigrants towards the majority society in Germany.The findings show that there is a strong relationship between experiences of discrimination and a hostile or alienated attitude towards German society. As an attempt to explain this generalization from single incidents to the macro relation between immigrants and autochthonous Germans in general a theory of framing, taken from developments in the field of rational choice theory, is applied. The reasoning is that a generalizing and rather hostile framing in terms of the attitude towards Germans can minimize psychic, emotional and social costs resulting from acts of discrimination.